Village Fund Allocation Information System for Community Empowerment in Klambir Lima Kebun Village - Randi Rian Putra; Nadya Andhika Putri; Cendra Wadisman (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
This study aims to provide information to the public about village funds that are applied to an online information system, in order to realize accountability and transparency of the budget of funds in the village. The procedure used is a descriptive qualitative research procedure and uses research information methods by observation, interviews, and documentation. The place of research to be conducted is in the village of Klambir Lima Gardens which is one of the villages located in the expanse of silver sub-district, Deli Serdang district, Medan city, North Sumatra. In line with the growth of people's expertise in development and the reduction of central government intervention in the region, so that development should be shown to change people's lives for the better. the type of project to be managed and the distribution of village fund allocations received by the village government to be used for operational costs for the administration of the village government, with the existence of an information system that can provide information about activities in the village and the form of village funds in the village of klambir lima gardens